Emerging new accents : a perspective of gender and development in Bangladesh - Duza, Asfia; Begum, Hamida A.; Women for Women (Organization : Bangladesh) (Dhaka : Women for Women, 1993)
On Bangladesh women in literature.
Includes bibliographical references (p. 89-92).
Robin
Keywords: Women -- Government policy -- Bangladesh; Women in development -- Bangladesh